Rancang Bangun Alat Pengaman Sepeda Motor Menggunakan Global Positioning System (GPS) Berbasis IoT - zainal abidin (Journal of Electrical Engineering and Computer (JEECOM), 2020)
The developments of technology have penetrated into various fields including motorcycle safety. The manufacturer’s standard of locking system is not enough to protect the motor vehicles from theft. Therefore, it requires a combination between software and hardware in creating additional security systems. The purpose of this study is to design a motorcycle safety device by using IoT-based GPS. The system is designed in order to control the motorcycle automatically turn the engine off, sound the horn, and detect the location of motorcycle by smartphone with Blynk application when the robbery happened. Optocoupler sensor is a tool that uses to send a notification to Blynk application when the motorcycle is stolen. It uses the Neo6mv2 GPS sensor as a coordinate sensor, NodeMCU V3 Microcontroller as a data processor and communication with a WiFi modem, Bolt brand WiFI modem as a link to the internet network and Relay as a button that is controlled by the Blynk application to turn on or turn off the engine, horn and turn signal. All of the components require a supply 5V voltage that generated by the motor ACCU 12V which is reduced to 5V by LM2596 module.